(untitled) (Tempo e Argumento, 2024)
Attacks on public monuments, particularly monuments representing infamous pasts that perpetuate memories of racism and colonial violence in the present, have provoked intense debate in recent years. With this background, this article discusses the place of public monuments in politics of cultural heritage, reflecting on how these politics mobilize reason and emotion, as well as bringing the present time closer to its multiple pasts. The first part problematizes the pain caused by the presence of monuments which, in their symbolic force, perpetuate memories of violence against oppressed groups. It thus addresses the presence of the past and the emotions arising from this presence. In the second part, we return to the idea of loss, but not in the rhetorical sense that has already been addressed in the history of heritage, but around the effects of commotions in the face of what has ceased or may cease to exist. Thus, the debate shifts from reflecting on emotions in the face of the presence of the past to problematizing the emotions caused by the recognition that the past has become an absence. In this way, we seek to reflect on the overlapping times of heritage, mobilizing the notions of nostalgia and mourning in the interpolation between the irreversible and the irrevocable of the past. In the final remarks, attention is drawn to the place of politics of heritage in a History of the Present Time, with a view to understanding how the profanations of monuments create ephemeral appearance spaces for histories and memories of invisibilized subjects and groups to appear.